Rediscovering the history of economic thought - Backhouse, RE; Forder, J (Royal Economic Society, 2021)
A recent issue of Oxford Economic Papers used the fiftieth anniversary of the British Hitory of Economic Thought Conference to reflect on the reawakening of interest in the history of economic ideas that has accompanied the movement of the twentieth century from ‘the present’ to ‘the past’. Roger Backhouse and James Forder look at reasons for that reawakening and add some arguments of their own in support of the trend.